A test of three basic assumptions of Situational Leadership® II Model and their implications for HRD practitioners. Issue 3 (3rd April 2017) - Zigarmi, Drea; Roberts, Taylor Peyton
Abstract : Purpose: This study aims to test the following three assertions underlying the Situational Leadership® II (SLII) Model: all four leadership styles are received by followers; all four leadership styles are needed by followers; and if there is a fit between the leadership style a follower receives and needs, that follower will demonstrate favorable scores on outcome variables. Design/methodology/approach: For the first and second assertions, a proportional breakdown of the four leadership styles observed within a sample of working professionals is presented and discussed. Regarding the third assertion, for ten outcome variables, multiple one-way analyses of variance tested mean differences between followers who experienced leadership style fit (i.e. a fit between received and needed style) and followers who did not experience fit ( n = 573). Subscale scores from the Leader Action Profile, the Work Intention Inventory, the Positive and Negative Affect Scale and an adapted form of the Affective/Cognitive trust scale (McAllister, 1995) were used as study measures. Findings: Three of the four leadership styles of the SLII framework were reported as frequently received. All four of the leadership styles were reported as needed. This study also found that follower-reported fit between one's needed and received leadership style at work resulted in more favorable scores on nine of the ten employee outcomes, as compared to follower-reported misfit. Practical implications: As human resource development practitioners seek to educate and train their leaders on how to be more effective with their direct reports, this research provides evidence that all four styles are needed and received, although there were lower instances of reporting the S1 style to be needed or received. Also, the findings demonstrated that when followers view a fit exists between the leadership behaviors they need and the leadership behaviors they receive, greater positive job affect, lower negative job affect, increased cognitive and affective trust in the leader and higher levels of favorable employee work intentions were evident. Originality/value: This paper builds on the resurgence of studies examining initiating structure and consideration as leader behaviors. This is one of very few recent studies that, by combining initiating structure and consideration, reinvestigates the four leadership styles established by past contingency theories. Specifically, the authors used the SLII framework as a foundation for analysis. Overall, the study supports three of the major assumptions of the SLII framework.